Efektifitas Teknik Kompres Air Hangat dan Air Dingin Terhadap Bendungan Asi Pada Ibu Post Partum di TPMB Bidan A Kecamatan Babelan Kabupaten Bekasi Tahun 2023 - Yayah Hilmiah; Lili Farlikhatun (Malahayati Nursing Journal, 2024)
ABSTRACT The incidence of ASI dams caused by the release of milk that is not smooth, because the baby does not feed his mother often enough. An initial survey conducted in April 2023 at TPMB Midwife A, Babelan District, Bekasi Regency, in 2023 found that there were 20 postpartum mothers who experienced ASI dams. To determine the effectiveness of giving warm and cold water compresses to breast milk dams in postpartum mothers. This study used a quasi-experimental with purposive sampling with a sample of 32 people. Data techniques included in uivariate analysis using frequency distribution and bivariate analysis using SPSS program statistical calculations. The results of this study indicate that the value of the Paired Sample Test obtained a sig (2-tailed) value of 0.000 0.05, so there is a difference between the pretest and posttest values so that it can be concluded that there is an effectiveness of giving warm compresses and cold compresses to breast milk dams for Postpartum Mothers at TPMB Midwife A, Babelan District, Bekasi Regency in 2023. There is an effectiveness of giving warm compresses and cold compresses to breast milk dams for Postpartum Mothers at TPMB Midwife A, Babelan District, Bekasi Regency in 2023. It is hoped that the method of giving warm compresses and compresses cold as a reference for intervention against breast milk in postpartum mothers. Keywords: Compression Techniques, Cold Water, Warm Water, Breast Milk Dams, Post Partum Mothers  ABSTRAK Kejadian bendungan ASI yang disebabkan oleh pengeluaran air susu yang tidak lancar, karena bayi tidak cukup sering menyusui pada ibu nya. Survei awal yang dilakukan pada bulan April 2023 di TPMB Bidan A Kecamatan Babelan Kabupaten Bekasi Tahun 2023 didapatkan ada 20 ibu nifas yang mengalami bendungan ASI. Mengetahui efektifitas pemberian kompres air hangat dan air dingin terhadap bendungan ASI pada ibu Post Partum. Penelitian ini menggunakan quasi esperimental dengan purposive sampling dengan sample 32 orang. Teknik data termasuk dalam analisis uivariat menggunakan distribusi frekuensi dan analisis bivariat menggunakan perhitungan statistik program SPSS. Hasil dari penelitian ini menunjukkan bahwa nilai Paired Sampel Test didapatkan nilai sig (2-tailed) adalah 0,000 0,05 maka terdapat perbedaan antara nilai pretest dan posttest sehingga dapat disimpulkan adanya efektifitas pemberian kompres hangat dan kompres dingin terhadap bendungan ASI pada Ibu Postpartum di TPMB Bidan A Kecamatan Babelan Kabupaten Bekasi Tahun 2023. Terdapat efektifitas pemberian kompres hangat dan kompres dingin terhadap bendungan ASI pada Ibu Postpartum di TPMB Bidan A Kecamatan Babelan Kabupaten Bekasi Tahun 2023. Diharapkan metode pemberian kompres hangat dan kompres dingin sebagai acuan intervensi terhadap bendungan ASI pada Ibu Postpartum. Kata Kunci: Teknik Kompres, Air Dingin, Air Hangat, Bendungan ASI, Ibu Post Partum